Local Election in Nepal: Means for Ensuring Electoral Accountability - Paudel, Narendra Raj; Pahari, Srijana (Journal of APF Command and Staff College, 2020)
The electoral accountability is considered a mechanism through which voters hold the government responsible for their performance. The main assumption in this article is that the more performance of local representatives as per their promise before elections under prevailing laws likely leads to more electoral accountability. To test this hypothesis, 455 questionnaires were collected from ordinary citizens and 28 interviews were taken with respective Rural Municipalities and Municipality’s chief, deputy chief, and an executive from Sindhuli and Surkhet district of Nepal. The result showed that the performance of Surkhet districts’ local governments have a better significant relationship with the electoral accountability index rather Sindhuli district. Despite this relationship, people were neither satisfied, nor unsatisfied with the performance of the local representatives. There are a lot of hindering factors associated with the performance of local representatives which include lack of financial resources, lack of knowledge on how to handle local government, lack of employees, lack of infrastructure, etc. Therefore, the study concludes that electoral accountability in Nepal is in the transitional stage.